Cr-spinel Mineral Chemistry from Sawlava Ophiolite Complex, Kurdistan, NW Iran, Geotectonic Setting Implication - Rahimzadeh, Bahman; Masoudi, Fariborz; Shabani, Amir Ali Tabbakh (Sulaimani Journal for Pure and Applied Sciences, 2016)
Ophiolitic ultramafic rocks associated with chromitite lenses are studied in detail from Sawlava ophiolitic complex along the Zagros suture in the northwest of Iran. Except one small window in Miana village almost all primary silicates in dunites and wehrlites have been altered to serpentine; however, Cr-spinel is the surviving phase left. Chemistry of the Cr-spinel minerals from small chromitite lenses within the ultramafic units provides information about the primary petrological characteristics. The Cr# of the Cr-spinels is between 0.76 to 0.82 in chromitite lenses, 0.58 to 0.67 in dunite and 0.49 to 0.52 in wehrlite. Al2O3 values and FeO/MgO ratio in the chromitite lenses indicate a boninitic melt for the source magmas of the Cr-spinels. The low values of Ti and high contents of Al and high Cr# in peridotite Cr-spinels reveal a pronounced rate of partial melting (25-35%) for peridotites. This suggests that Sawlava complex source was mantle wedge with elevated degrees of partial melting. Olivine, clinopyroxene and Cr-spinel mineral chemistry shows the characterization similar to those in abyssal to supra- subduction zone (SSZ) peridotites which suggest a fore-arc basin setting for the generation of the chromitite lenses from Sawlava ophiolites.
Keywords: CrSpinel,Chromitite; Sawlavaophiolitic complex,Zagros; Iran